2021
DOI: 10.1111/jipb.13088
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of MaMYB16L regulates starch degradation in banana fruit during ripening

Abstract: The alternative splicing of select genes is an important mechanism to regulate responses to endogenous and environmental signals in plants. However, the role of alternative splicing in regulating fruit ripening remains unclear. Here, we discovered that MaMYB16L, an R1‐type MYB transcription factor, undergoes alternative splicing and generates two transcripts, the full‐length isoform MaMYB16L and a truncated form MaMYB16S, in banana fruit. During banana fruit ripening, the alternative splicing process intensifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…AS has been proven to play important roles in a variety of plant processes, including fruit ripening [ 11 15 ]. In maize ( Zea mays L.), researchers have found that missplicing of U12-type introns in rgh3 can cause aberrant endosperm cell differentiation and proliferation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…AS has been proven to play important roles in a variety of plant processes, including fruit ripening [ 11 15 ]. In maize ( Zea mays L.), researchers have found that missplicing of U12-type introns in rgh3 can cause aberrant endosperm cell differentiation and proliferation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we found that at least 6,266 genes underwent AS during watermelon fruit ripening (data not shown). Most recently, MaMYB16L was reported to regulate starch degradation by alternative splicing in banana fruit during ripening ( Jiang et al, 2021 ). These results support the potential post-transcriptional and post-translational mechanisms in regulation of fruit ripening, which have also been described in other fruits, such as tomato, sweet orange and citrus ( Osorio et al, 2011 ; Pan et al, 2012 ; Wu et al, 2014b ; Belouah et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression characteristics of different transcripts produced by the same gene, the functional positions of proteins coding by these transcripts, and the biological functions of these proteins may be different [ 37 , 38 ]. Previous studies have shown that MaMYB16 produces two transcripts, MaMYB16L and MaMYB16S , with opposite functions in controlling fruit ripening through alternative splicing [ 39 ]. MaMYB16L is a transcription inhibitor that inhibits fruit ripening by directly downregulating the expression of MaDREB2 ; MaMYB16S loses the ability to bind to DNA, but can bind to MaMYB16L competitively, and then form inactive dimers that ultimately promote fruit ripeness.…”
Section: Discussionmentioning
confidence: 99%